Preparation method of ceramic lanthanum titanate coating material and prepared ceramic lanthanum titanate

Through the optimization of specific ratio and sintering process, the problems of purity and evaporation stability of ceramic lanthanum titanate coating materials are solved, and the preparation of ceramic lanthanum titanate coating materials with high purity and good stability are achieved.

CN119613104APending Publication Date: 2025-03-14CHANGZHOU PROSRUN PHOTOELECTRIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411753875.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The purity of the existing ceramic lanthanum titanate coating materials is difficult to reach more than 99.95%, and the evaporation process is unstable, and the refractive index is prone to drift.

Method used

Through the mixing, granulation and sintering processes of titanium dioxide, lanthanum oxide and titanium powder with specific ratios, the sintering temperature and time are controlled, and the heating and cooling rate in the furnace body and furnace are optimized to improve the purity and evaporation stability of the ceramic lanthanum titanate coating material.

Benefits of technology

The purity of the ceramic lanthanum titanate coating material is achieved to reach 99.99%, and its evaporation stability is improved, ensuring the small change rate of vacuum and the stability of refractive index.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613104A_ABST
    Figure CN119613104A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a ceramic lanthanum titanate coating material and prepared ceramic lanthanum titanate, and relates to the field of coating materials. The preparation method of the ceramic lanthanum titanate coating material comprises the following steps: S1, material mixing: weighing titanium dioxide, lanthanum oxide and titanium powder according to a ratio, and uniformly mixing to obtain a premix; s2, granulation: sequentially carrying out cake pressing and crushing steps on the premix to obtain particles; and S3, sintering: sintering the particles in a vacuum sintering furnace at the sintering temperature of 1650-1750 DEG C for 4-20 hours, and crushing and screening the sintered material to obtain the ceramic lanthanum titanate coating material. The ceramic lanthanum titanate coating material has the advantages of being high in purity, good in evaporation stability and high in adhesion fastness to a substrate material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coating materials, and in particular to a ceramic lanthanum titanate coating material, a preparation method thereof, and the obtained ceramic lanthanum titanate. Background Art

[0002] Ceramic lanthanum titanate is widely used in the optical film industry due to its unique physical properties. However, at present, when preparing ceramic lanthanum titanate coating materials, it is usually faced with the problem that the purity of ceramic lanthanum titanate coating materials is difficult to reach above 99.95%, and it is even more difficult to reach 99.99%. In addition, the existing ceramic lanthanum titanate also has the problem of unstable evaporation process and easy drift of refractive index. Therefore, how to obtain a ceramic lanthanum titanate coating material with high purity and stable evaporation is of great research significance. Summary of the invention

[0003] In order to improve the purity and evaporation stability problems of ceramic lanthanum titanate coating materials in the related art, the present application provides a ceramic lanthanum titanate coating material and a preparation method thereof and the prepared ceramic lanthanum titanate.

[0004] In the first aspect, the present application provides a method for preparing a ceramic lanthanum titanate coating material using the following technical solution: A method for preparing a ceramic lanthanum titanate coating material comprises the following steps: S1. Mixing: Weigh titanium dioxide, lanthanum oxide and titanium powder according to the ratio, mix them evenly, and obtain a premix; wherein the raw material of titanium dioxide accounts for 31.2-31.8wt%, the raw material of lanthanum oxide accounts for 66.5-67.0wt%, and the raw material of titanium powder accounts for 1.7-1.8wt%; S2, granulation: the premix is ​​subjected to cake pressing and crushing steps in sequence to obtain granules; S3. Sintering: put the particles into a vacuum sintering furnace, turn on the mechanical pump and the Roots pump, and when the vacuum degree in the furnace reaches below 15Pa, start the furnace heating. When the temperature in the furnace reaches 1500-1600℃ and the vacuum degree reaches below 15Pa, turn on the diffusion pump for heating. When the vacuum degree reaches below 0.1Pa, control the temperature in the furnace to 1650-1750℃ and keep it warm for 4-20h. Then turn off the heating power supply and cool down the temperature in the furnace. When the temperature in the furnace drops below 50℃, take out the molybdenum container, crush and sieve the sintered material in the molybdenum container to obtain a ceramic lanthanum titanate coating material.

[0005] The ceramic lanthanum titanate coating material of the present application is obtained by mixing, granulating and sintering titanium dioxide, lanthanum oxide and titanium powder in a specific ratio. Among them, the addition of titanium powder in a specific ratio and the specific sintering process are conducive to accelerating the reaction rate, promoting the formation of ceramic lanthanum titanate, and improving the purity of the ceramic lanthanum titanate coating material. In addition, it is also conducive to reducing the oxygen content in the ceramic lanthanum titanate coating material, reducing the amount of outgassing during the evaporation process, and promoting the stable evaporation process. It is conducive to obtaining a ceramic lanthanum titanate coating material with high adhesion to the substrate and good evaporation stability (small vacuum change rate and stable refractive index).

[0006] In some specific embodiments, in step S2, the size of the particles is controlled to be 1-5 mm.

[0007] In the present application, the size of the particles is controlled to be 1-5 mm, which is beneficial to promote the reaction of titanium dioxide and lanthanum oxide in the particles to form ceramic lanthanum titanate, and reduce the impurity content in the ceramic lanthanum titanate coating material, which is beneficial to improve the purity and evaporation stability of the ceramic lanthanum titanate coating material (small vacuum change rate and stable refractive index).

[0008] In some specific embodiments, in step S2, the size of the particles is controlled to be 1-2 mm.

[0009] In the present application, controlling the size of the particles to 1-2 mm is beneficial to further improve the purity of the ceramic lanthanum titanate, thereby improving the evaporation stability of the ceramic lanthanum titanate coating material (small vacuum degree change rate and stable refractive index).

[0010] In some specific embodiments, in step S3, when the furnace is turned on for heating, before the furnace is heated to 500°C, the heating rate of the furnace is controlled to be 2-8°C / min, when the furnace temperature is between 500-1000°C, the heating rate of the furnace is controlled to be 10-15°C / min, and when the furnace temperature is greater than 1000°C, the heating rate of the furnace is controlled to be 0.5-3°C / min; In step S3, when cooling the temperature in the furnace, first control the cooling rate of the furnace temperature at 1-5°C / min. When the temperature in the furnace drops to 1200°C, control the cooling rate of the furnace to 10-15°C / min. When the temperature in the furnace drops to 850°C, control the cooling rate of the furnace to 1-5°C / min until the temperature in the furnace drops below 50°C.

[0011] In the present application, controlling the heating rate of the furnace body at each stage is beneficial to protecting the integrity of the particle structure and preventing the particle from splitting on the one hand, and is beneficial to the escape of volatile impurity materials in the raw materials on the other hand, which is beneficial to further improve the purity of the ceramic lanthanum titanate coating material. Controlling the cooling rate at each stage in the furnace is beneficial to promoting the formation of ceramic lanthanum titanate, reducing the content of impurities, and further improving the purity of the ceramic lanthanum titanate coating material. In addition, through the coordination of the heating rate of the furnace body at each stage and the cooling rate of the furnace at each stage, it is beneficial to further improve the evaporation stability of the ceramic lanthanum titanate coating material (small vacuum change rate and stable refractive index).

[0012] Preferably, in step S3, when the furnace is turned on for heating, before the furnace is heated to 500°C, the heating rate of the furnace is controlled to be 2-4°C / min, when the furnace temperature is between 500-1000°C, the heating rate of the furnace is controlled to be 10-12°C / min, and when the furnace temperature is greater than 1000°C, the heating rate of the furnace is controlled to be 1-2°C / min; In step S3, when cooling the temperature in the furnace, first control the cooling rate of the furnace temperature at 4-5°C / min. When the temperature in the furnace drops to 1200°C, control the cooling rate of the furnace to 10-12°C / min. When the temperature in the furnace drops to 850°C, control the cooling rate of the furnace to 1-2°C / min, until the temperature in the furnace drops below 50°C.

[0013] Among them, the longer the sintering time, the higher the purity of the ceramic lanthanum carbonate coating material, but it is currently a difficult problem to produce a ceramic lanthanum titanate coating material with a purity of 99.99% in a shorter sintering time. In this application, by optimizing the heating rate of the furnace body at each stage and the cooling rate of the furnace at each stage, the purity of the ceramic lanthanum titanate coating material can reach 99.99% when the sintering time reaches 4 hours. At the same time, the evaporation stability of the ceramic lanthanum titanate coating material can be further improved (small vacuum change rate and stable refractive index).

[0014] Preferably, before performing step S1, titanium dioxide, lanthanum oxide and titanium powder are respectively sieved through an 80-mesh sieve to remove the residue.

[0015] Preferably, in step S3, the particle size range of the ceramic lanthanum titanate coating material obtained is 1-2 mm.

[0016] In a second aspect, a ceramic lanthanum titanate coating material provided in the present application adopts the following technical solution.

[0017] A ceramic lanthanum titanate coating material is prepared from any one of the above-mentioned ceramic lanthanum titanate coating materials.

[0018] The ceramic lanthanum titanate coating material of the present application has the advantages of high purity, good evaporation stability, and high adhesion to the substrate material.

[0019] In summary, this application at least includes the following beneficial technical effects: (1) The ceramic lanthanum titanate coating material of the present application is obtained by mixing titanium dioxide, lanthanum oxide and titanium powder in a specific ratio, granulating and sintering. Among them, the addition of titanium powder in a specific ratio and the specific sintering process are conducive to accelerating the reaction rate, promoting the formation of ceramic lanthanum titanate, and improving the purity of the ceramic lanthanum titanate coating material. In addition, it is also conducive to reducing the oxygen content in the ceramic lanthanum titanate coating material, reducing the amount of outgassing during the evaporation process, and promoting the stable evaporation process, which is conducive to obtaining a ceramic lanthanum titanate coating material with high adhesion to the substrate and good evaporation stability.

[0020] (2) In the present application, by optimizing the heating rate of the furnace body at each stage and optimizing the cooling rate of the furnace at each stage, the purity of the ceramic lanthanum titanate coating material can reach 99.99% within a sintering time of 4 hours. At the same time, the evaporation stability of the ceramic lanthanum titanate coating material can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a product picture of the ceramic lanthanum titanate coating material of this application. DETAILED DESCRIPTION

[0022] The present application is further described below in conjunction with specific experiments. Among them, the titanium dioxide used in each embodiment of the present application is high-purity titanium dioxide from Hebei Teng Bimetallic Materials Co., Ltd., the lanthanum oxide used is high-purity lanthanum oxide from Hebei Teng Bimetallic Materials Co., Ltd., and the titanium powder used is high-purity metal titanium powder from Hebei Teng Bimetallic Materials Co., Ltd. Example

[0023] [Example 1] A ceramic lanthanum titanate coating material, the preparation method of which comprises the following steps: S1, mixing: before performing step S1, first pass titanium dioxide, lanthanum oxide and titanium powder through an 80-mesh sieve respectively, remove the sieve residue, weigh titanium dioxide, lanthanum oxide and titanium powder respectively according to the ratio, mix them well, and obtain a premix; wherein the raw material of titanium dioxide accounts for 31.2wt%, the raw material of lanthanum oxide accounts for 67.0wt%, and the raw material of titanium powder accounts for 1.8wt%; S2, granulation: the premix is ​​subjected to cake pressing and crushing steps in sequence to obtain granules with a particle size range of 1-2 mm; S3. Sintering: The particles are loaded into a container (the melting point of the container is greater than the sintering temperature, for example, a molybdenum crucible, a graphite crucible, a tungsten crucible, etc. can be used. The container used in this embodiment is specifically a molybdenum crucible), and placed in a vacuum sintering furnace. The mechanical pump and the Roots pump are turned on. When the vacuum degree in the furnace reaches below 15 Pa, the furnace body is turned on for heating. The heating rate of the furnace body is controlled to be 8°C / min. When the temperature in the furnace reaches 1500°C and the vacuum degree reaches below 15 Pa, the diffusion pump is turned on for heating. When the vacuum degree reaches below 0.1 Pa, the temperature in the furnace is controlled to be 1650°C and kept warm for 4 hours. Then the heating power is turned off, the temperature in the furnace is cooled down, and the cooling rate in the furnace is 5°C / min. When the temperature in the furnace drops below 50°C, the molybdenum container is taken out, and the sintered material in the molybdenum container is crushed and sieved to obtain a ceramic lanthanum titanate coating material with a particle size range of 1-2 mm and a purity of 99.65%.

[0024] [Example 2] A ceramic lanthanum titanate coating material, the preparation method of which comprises the following steps: S1, mixing: before performing step S1, first pass titanium dioxide, lanthanum oxide and titanium powder through an 80-mesh sieve respectively, remove the sieve residue, weigh titanium dioxide, lanthanum oxide and titanium powder respectively according to the ratio, mix them well, and obtain a premix; wherein the raw material of titanium dioxide accounts for 31.8wt%, the raw material of lanthanum oxide accounts for 66.5wt%, and the raw material of titanium powder accounts for 1.7wt%; S2, granulation: the premix is ​​subjected to cake pressing and crushing steps in sequence to obtain granules with a particle size range of 1-2 mm; S3. Sintering: put the particles into a container (the melting point of the container is greater than the sintering temperature, for example, a molybdenum crucible, a graphite crucible, a tungsten crucible, etc. can be used. The container used in this embodiment is specifically a molybdenum crucible), and put it into a vacuum sintering furnace, turn on the mechanical pump and the Roots pump, and when the vacuum degree in the furnace reaches below 15Pa, turn on the furnace body heating, and the heating rate of the furnace body is controlled to be 5°C / min. When the temperature in the furnace reaches 1600°C and the vacuum degree reaches below 15Pa, turn on the diffusion pump for heating. When the vacuum degree reaches below 0.1Pa, control the temperature in the furnace to 1750°C and keep it warm for 4 hours. Then turn off the heating power supply, cool the temperature in the furnace, and the cooling rate in the furnace is 8°C / min. When the temperature in the furnace drops below 50°C, take out the molybdenum container, crush and sieve the sintered material in the molybdenum container to obtain a ceramic lanthanum titanate coating material with a particle size range of 1-2mm and a purity of 99.62%.

[0025] [Example 3] A ceramic lanthanum titanate coating material, which differs from [Example 1] in that: In step S3, when the temperature in the furnace is cooled down, before the furnace body is heated to 500°C, the heating rate of the furnace body is controlled to be 2°C / min. When the furnace body temperature is between 500-1000°C, the heating rate of the furnace body is controlled to be 10°C / min. When the furnace body temperature is greater than 1000°C, the heating rate of the furnace body is controlled to be 1°C / min.

[0026] The purity of the ceramic lanthanum titanate coating material prepared in this embodiment is 99.78%.

[0027] [Example 4] A ceramic lanthanum titanate coating material, which differs from [Example 3] in that: In step S3, when cooling the temperature in the furnace, first control the cooling rate in the furnace at 5°C / min. When the temperature in the furnace drops to 1200°C, control the cooling rate in the furnace to 10°C / min. When the temperature in the furnace drops to 850°C, control the cooling rate in the furnace to 1°C / min, until the temperature in the furnace drops below 50°C.

[0028] The purity of the ceramic lanthanum titanate coating material prepared in this embodiment is 99.99%.

[0029] [Example 5] A ceramic lanthanum titanate coating material, which differs from [Example 4] in that: Among them, in step S3, when the temperature in the furnace is cooled down, before the furnace body is heated to 500°C, the heating rate of the furnace body is controlled to be 4°C / min. When the furnace body temperature is between 500-1000°C, the heating rate of the furnace body is controlled to be 12°C / min. When the furnace body temperature is greater than 1000°C, the heating rate of the furnace body is controlled to be 2°C / min.

[0030] In addition, in step S3, when the temperature in the furnace is cooled, the cooling rate in the furnace is first controlled at 4°C / min. When the temperature in the furnace drops to 1200°C, the cooling rate in the furnace is controlled to 12°C / min. When the temperature in the furnace drops to 850°C, the cooling rate in the furnace is controlled to 2°C / min, until the temperature in the furnace drops below 50°C.

[0031] The purity of the ceramic lanthanum titanate coating material prepared in this embodiment is 99.99%.

[0032] [Example 6] A ceramic lanthanum titanate coating material, which differs from [Example 4] in that: In step S3, before the furnace body is heated to 500°C, the heating rate of the furnace body is controlled to be 6°C / min. When the furnace body temperature is between 500-1000°C, the heating rate of the furnace body is controlled to be 15°C / min. When the furnace body temperature is greater than 1000°C, the heating rate of the furnace body is controlled to be 3°C / min.

[0033] The purity of the ceramic lanthanum titanate coating material prepared in this embodiment is 99.92%.

[0034] [Example 7] A ceramic lanthanum titanate coating material, which differs from [Example 4] in that: In step S3, before the furnace body is heated to 500°C, the heating rate of the furnace body is controlled to be 8°C / min. When the furnace body temperature is between 500-1000°C, the heating rate of the furnace body is controlled to be 15°C / min. When the furnace body temperature is greater than 1000°C, the heating rate of the furnace body is controlled to be 0.5°C / min.

[0035] The purity of the ceramic lanthanum titanate coating material prepared in this embodiment is 99.94%.

[0036] [Example 8] A ceramic lanthanum titanate coating material, which differs from [Example 4] in that: In step S3, when cooling the temperature in the furnace, first control the cooling rate of the furnace temperature at 1°C / min. When the temperature in the furnace drops to 1200°C, control the cooling rate of the furnace to 15°C / min. When the temperature in the furnace drops to 850°C, control the cooling rate of the furnace to 1°C / min, until the temperature in the furnace drops below 50°C.

[0037] The purity of the ceramic lanthanum titanate coating material prepared in this embodiment is 99.93%.

[0038] [Example 9] A ceramic lanthanum titanate coating material, which differs from [Example 4] in that: In step S3, when cooling the temperature in the furnace, first control the cooling rate of the furnace temperature at 5°C / min. When the temperature in the furnace drops to 1200°C, control the cooling rate of the furnace to 15°C / min. When the temperature in the furnace drops to 850°C, control the cooling rate of the furnace to 5°C / min, until the temperature in the furnace drops below 50°C.

[0039] The purity of the ceramic lanthanum titanate coating material prepared in this embodiment is 99.91%.

[0040] Comparative Example [Comparative Example 1] A ceramic lanthanum titanate coating material, which differs from [Example 1] in that: In step S1, no titanium powder was added.

[0041] The purity of the ceramic lanthanum titanate coating material prepared in this comparative example is 99.01%.

[0042] [Comparative Example 2] A ceramic lanthanum titanate coating material, which differs from [Example 1] in that: In step S3, the heat preservation time in the furnace is 3 hours.

[0043] The purity of the ceramic lanthanum titanate coating material prepared in this comparative example is 99.12%.

[0044] Preparation of performance test samples: The ceramic lanthanum titanate coating materials prepared in the above embodiments and comparative examples were evaporated on a BK7 substrate using a Japanese SuperAR-1300 coating machine. The initial vacuum degree was controlled to 4.0×10 -3 Pa, the evaporation rate of ceramic lanthanum titanate coating material is 4A / s, and the film thickness is 1.5KA.

[0045] 1. Vacuum degree change rate: record the maximum change rate of the vacuum degree of the coating machine during the evaporation process. The greater the change rate of the vacuum degree, the more gas released by the ceramic lanthanum titanate during the evaporation process, and the greater the impact on the evaporation stability.

[0046] 2. Moisture and heat resistance test of film layer: The samples prepared in each embodiment and comparative example are placed in a humidity and heat test chamber, and the temperature of the test chamber is uniformly increased from -20°C to 80°C within 2 hours, and then uniformly decreased from 80°C to -20°C within 2 hours, which is recorded as one cycle. After recording the 12th and 18th cycles respectively, 10 samples that have completed the humidity and heat resistance test and have intact film layers are randomly selected from each group of samples as the test samples for refractive index testing at 500nm. The refractive index change rate of the test samples before and after the humidity and heat resistance test is within the range of ±0.5%, which is considered to be stable without drift. The number of samples with no refractive index drift is recorded, among which, more than 80% of the 10 test samples with no refractive index drift are considered qualified.

[0047] 3. Film adhesion strength: For each group of samples, 10 samples that have completed the moisture and heat resistance test and have intact films are randomly selected as the samples to be tested. Wipe the same position of each lanthanum titanate film with 2kg of force and rub it back and forth 25 times with acetone on the wipe paper; then use the tape to stick to the surface of the lanthanum titanate film, and quickly tear off the tape at 90 degrees, repeat 3 times at the same position, and record the number of samples with peeled films. Among them, more than 90% of the 10 samples to be tested have no film peeling phenomenon and are considered qualified.

[0048] Table 1 Combining the contents of Comparative Examples 1-2 and Example 1 and the test data in Table 1, it can be seen that the addition of titanium powder and the control of sintering time will affect the purity and evaporation stability of the lanthanum titanate coating material of the present application.

[0049] Combined with the contents recorded in Example 1, Examples 3-9 and the test data in Table 1, it can be seen that: in step S3, when the furnace body is turned on for heating, before the furnace body is heated to 500°C, the heating rate of the furnace body is controlled to be 2-4°C / min, when the furnace body temperature is between 500-1000°C, the heating rate of the furnace body is controlled to be 10-12°C / min, and when the furnace body temperature is greater than 1000°C, the heating rate of the furnace body is controlled to be 1-2°C / min; when the temperature in the furnace is cooled, the cooling rate of the furnace temperature is first controlled at 4-5°C / min, when the furnace temperature drops to 1200°C, the cooling rate of the furnace is controlled to be 10-12°C / min, when the furnace temperature drops to 850°C, the cooling rate of the furnace is controlled to be 1-2°C / min, until the furnace temperature drops below 50°C, the purity of the ceramic lanthanum titanate coating material can reach more than 99.99%, and at the same time, the evaporation stability of the ceramic lanthanum titanate coating material can be further improved.

[0050] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a ceramic lanthanum titanate coating material, characterized in that: The following steps are involved: S1. Mixing: Weigh titanium dioxide, lanthanum oxide and titanium powder according to the ratio, mix them evenly, and obtain a premix; wherein the raw material of titanium dioxide accounts for 31.2-31.8wt%, the raw material of lanthanum oxide accounts for 66.5-67.0wt%, and the raw material of titanium powder accounts for 1.7-1.8wt%; S2, granulation: the premix is ​​subjected to cake pressing and crushing steps in sequence to obtain granules; S3. Sintering: put the particles into a vacuum sintering furnace, turn on the mechanical pump and the Roots pump, and when the vacuum degree in the furnace reaches below 15Pa, start the furnace heating. When the temperature in the furnace reaches 1500-1600℃ and the vacuum degree reaches below 15Pa, turn on the diffusion pump for heating. When the vacuum degree reaches below 0.1Pa, control the temperature in the furnace to 1650-1750℃ and keep it warm for 4-20h. Then turn off the heating power supply and cool down the temperature in the furnace. When the temperature in the furnace drops below 50℃, take out the molybdenum container, crush and sieve the sintered material in the molybdenum container to obtain a ceramic lanthanum titanate coating material.

2. The method for preparing a ceramic lanthanum titanate coating material according to claim 1, characterized in that: In step S2, the size of the particles is controlled to be 1-5 mm.

3. The method for preparing a ceramic lanthanum titanate coating material according to claim 2, characterized in that: In step S2, the size of the particles is controlled to be 1-2 mm.

4. The method for preparing a ceramic lanthanum titanate coating material according to claim 1, characterized in that: In step S3, when the furnace is turned on for heating, before the furnace is heated to 500°C, the heating rate of the furnace is controlled to be 2-8°C / min, when the furnace temperature is between 500-1000°C, the heating rate of the furnace is controlled to be 10-15°C / min, and when the furnace temperature is greater than 1000°C, the heating rate of the furnace is controlled to be 0.5-3°C / min; In step S3, when cooling the temperature in the furnace, first control the cooling rate of the furnace temperature at 1-5°C / min. When the temperature in the furnace drops to 1200°C, control the cooling rate of the furnace to 10-15°C / min. When the temperature in the furnace drops to 850°C, control the cooling rate of the furnace to 1-5°C / min until the temperature in the furnace drops below 50°C.

5. The method for preparing a ceramic lanthanum titanate coating material according to claim 4, characterized in that: In step S3, when the furnace is turned on for heating, before the furnace is heated to 500°C, the heating rate of the furnace is controlled to be 2-4°C / min, when the furnace temperature is between 500-1000°C, the heating rate of the furnace is controlled to be 10-12°C / min, and when the furnace temperature is greater than 1000°C, the heating rate of the furnace is controlled to be 1-2°C / min; In step S3, when cooling the temperature in the furnace, first control the cooling rate of the furnace temperature at 4-5°C / min. When the temperature in the furnace drops to 1200°C, control the cooling rate of the furnace to 10-12°C / min. When the temperature in the furnace drops to 850°C, control the cooling rate of the furnace to 1-2°C / min, until the temperature in the furnace drops below 50°C.

6. The method for preparing a ceramic lanthanum titanate coating material according to claim 1, characterized in that: Before performing step S1, titanium dioxide, lanthanum oxide and titanium powder are respectively passed through an 80-mesh sieve to remove the sieve residue.

7. The method for preparing a ceramic lanthanum titanate coating material according to claim 1, characterized in that: In step S3, the particle size range of the obtained ceramic lanthanum titanate coating material is 1-2 mm.

8. A ceramic lanthanum titanate coating material, characterized in that: It is made from the ceramic lanthanum titanate coating material described in any one of claims 1 to 7.